Exploring the experience of workplace qiling (bullying) in Shenzhen, China : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Management at Massey University, Albany, Auckland, New Zealand - Sun, Jishuo (Massey University, 2024)
Workplace bullying constitutes a significant and widespread concern that impacts the health and wellbeing of employees in numerous work environments globally. Although previous studies conducted in European countries have explored a dominant understanding of this issue, there is an increasing interest in the role of context (e.g., cultural and socioeconomic differences) in the understanding of workplace bullying. The Chinese context differs markedly from that of European countries, where the majority of the dominant research on bullying has been conducted to date. With a scarcity of bullying research specifically targeting the Chinese context, exploring how Chinese employees experience bullying will contribute to a more comprehensive understanding of this issue to better manage it in the Chinese workplace as well as globally. From the perspective of language, qiling is the Chinese term that has been used as the equivalent term for bullying. However, the academic understanding of qiling (in China) may be very different from the concept of bullying developed by scholars in European countries. Therefore, the objectives of this research were to understand the nature and development of workplace qiling from an employee’s perspective in a Chinese context (i.e., Shenzhen). Drawing on a pragmatic philosophical position, a constructivist grounded theory approach was used to address the research objectives. This study collected qualitative data through a semi-structured interview conducted virtually. It adopted three sampling methods—purposive, snowball, and theoretical sampling methods—to recruit participants. As a result, thirty-two participants, who were employees working in companies in Shenzhen and believed that they had either directly or indirectly experienced qiling within the last two years, were recruited for this study. Three stages of data analysis—initial, focused, and theoretical coding—were conducted to construct the findings from the collected data. The research findings contribute to an in-depth understanding of the nature and development of qiling in the workplace in Shenzhen. In terms of the nature of qiling, although its features were generally similar to the dominant understanding of workplace bullying, qiling behaviour is relatively invisible and subtle due to the influence of Chinese culture, and intention was considered by employees in Shenzhen as a crucial feature of qiling. In addition, the identified sources of power causing the power imbalance between perpetrators and targets included hierarchy, zili (seniority), and guanxi (relationship). The traditional Chinese belief of shi bu guo san (the rule of three times) was also identified regarding the frequency and duration of qiling. In terms of the development of qiling, the identified organisational antecedents can be grouped by involving Salin’s (2003) framework as a relevant sensitising concept: (1) enabling structures and processes (i.e., perceived power imbalance, adverse leadership styles, lack of sufficient management competencies, and coercive workplace culture); (2) motivating structures and processes (i.e., conflict of interest and neijuan (rat race)); and (3) precipitating processes (i.e., organisational changes). Although some of the organisational antecedents evident from the data overlapped with European theoretical frameworks, unique antecedents caused or influenced by Chinese culture and the characteristics of Shenzhen were identified. Overall, this study provides new insight into qiling in the Chinese context, which is equivalent to bullying. It also provides further evidence for the importance of contextual framing of workplace bullying in China and across different countries. The findings of this study are crucial because a thorough understanding of bullying is the cornerstone of developing prevention and intervention strategies to reduce the issue in the Chinese workplace, and it also contributes to knowledge about the global understanding and management of workplace bullying.
Keywords: Workplace bullying, Qiling, China, Employees, Constructivist grounded theory; Bullying in the workplace; China; Europe; Employees; Attitudes; workplace bullying; qiling; constructivist grounded theory